Biological Activities of Trunk Bark Extracts of Five Tree Species from Anatolia, Turkey - YAYLACI, FATMA; KOLAYLI, SEVGI; KUCUK, MURAT; ALPAY KARAOGLU, SENGUL; ULUSOY, ESRA (Asian Journal of Chemistry, 2010)
The antioxidant and antimicrobial capacity of the trunk bark extracts of five tree species, walnut (Juglans regia L.), pine (Pinus brutia Ten.), rhododendron (Rhododendron ponticum L.), juniper (Juniperus oxycedrus L.ssp.) and eucalyptus (Eucalyptus globulus L.), which were obtained from different regions of Anatolia, Turkey are investigated. Antioxidant-rich fractions were extracted from trunk-bark of the five species by using ethanol as solvent. Total antioxidant activity, ferric reducing/antioxidant power (FRAP), DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity and lipid peroxidation inhibitory activity of the extracts were studied. The total antioxidant activity of the extracts was evaluated by TLC-plate and ferric thiocyanate (FTC) methods. The total antioxidant activity and reducing power of the samples were concentration dependent. All the samples showed moderate to high antioxidant activity. The extracts also showed high radical scavenging activity. Pine and walnut extracts showed the highest inhibitory activity against lipid peroxide formation. Rhododendron was the least active in this respect. The antimicrobial activity of each extract was also studied with agar diffusion method using eight bacteria and two yeasts. Eucalyptus and walnut trunk-bark extracts showed considerably high antimicrobial activity against the microorganisms studied. All the extracts, especially those from walnut and juniper trunk bark proved to be a good source of antioxidants and to deserve further investigation as to their individual biologically active components, which may be an attractive source of nutraceutical supplements and of medicinal ingredients.